2021
DOI: 10.3897/dez.68.68020
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrenean species of Chelidura (Dermaptera, Forficulidae)

Abstract: The Pyrenees are inhabited by scattered populations of earwigs of the genus Chelidura Latreille, 1825. There is some controversy about the specific assignment of these populations: while most authors assign them to C. pyrenaica (Gené, 1832), other consider that C. aptera (Mégerlé, 1825) is also present in the Pyrenees. The main objective of this work was to revise the identity and synonyms of Pyrenean Chelidura. Specimens from recent fieldwork and collections (MNCN-CSIC) were used for morphological and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Defining evolutionary units using discrete traits is often a challenge because of problems overestimating phenotypic variability (Pomorski 1990;Jurado-Angulo et al 2021;Sottile et al 2022) or, on the contrary, underestimating it (Posso-Terranova & Andrés 2018;Sánchez-Vialas et al 2020). Pyrenean populations of Pseudochelidura have been treated as three different taxonomic units, P. sinuata, P. minor and P. montuosa, based on the shape of male cerci and pygidium (Steinmann 1979(Steinmann , 1981Caussanel et al 1990;Herrera Mesa 1999;Cuesta-Segura 2012), a set of characters widely used for taxonomic inference in Dermaptera Kočárek 2004;Anlaş & Kočárek 2012;Kirstová et al 2020;Fontana et al 2021b…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Defining evolutionary units using discrete traits is often a challenge because of problems overestimating phenotypic variability (Pomorski 1990;Jurado-Angulo et al 2021;Sottile et al 2022) or, on the contrary, underestimating it (Posso-Terranova & Andrés 2018;Sánchez-Vialas et al 2020). Pyrenean populations of Pseudochelidura have been treated as three different taxonomic units, P. sinuata, P. minor and P. montuosa, based on the shape of male cerci and pygidium (Steinmann 1979(Steinmann , 1981Caussanel et al 1990;Herrera Mesa 1999;Cuesta-Segura 2012), a set of characters widely used for taxonomic inference in Dermaptera Kočárek 2004;Anlaş & Kočárek 2012;Kirstová et al 2020;Fontana et al 2021b…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific variability of male cerci in earwigs is well known (Dohrn 1867;Diajonov 1925;Ollason 1970;Srivastava 1970;Mourier 1986;Simpson & Mayer 1990;Fontana et al 2021b;García-París et al 2021;Jurado-Angulo et al 2021); however, the levels of variability found in males of Pseudochelidura (Figs 2-3) are probably among the highest. It is thus somewhat counterintuitive that morphological differences in cerci shape between Pyrenean and Cantabrian populations (Figs 2-3) are relatively small and more limited than intrapopulational variability, but this is a situation relatively similar to that described for the French Massif Central and Pyrenean populations of Chelidura (Jurado-Angulo et al…”
Section: Pseudochelidura Cantabricamentioning
confidence: 97%
See 3 more Smart Citations